2021
DOI: 10.1111/iju.14650
|View full text |Cite
|
Sign up to set email alerts
|

Deep lateral transurethral incision for vesicourethral anastomotic stenosis after radical prostatectomy

Abstract: Abbreviations & Acronyms AUS = artificial urinary sphincter BCR = biochemical recurrence BMI = body mass index DLI = deep lateral incision DM = diabetes mellitus IHD = ischemic heart disease IQR = interquartile range LRP = laparoscopic radical prostatectomy RARP = robot-assisted radical prostatectomy RP = radical prostatectomy RRP = retropubic radical prostatectomy SPT = suprapubic tube UI = urinary incontinence VUAS = vesicourethral anastomotic stenosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…The risk of bias assessment was unfavourable for a large majority of studies regarding the measurement of the condition (utilisation of valid method, measurement in a standard, reliable way; Fig. 3 [1,19,27–64]).…”
Section: Resultsmentioning
confidence: 99%
“…The risk of bias assessment was unfavourable for a large majority of studies regarding the measurement of the condition (utilisation of valid method, measurement in a standard, reliable way; Fig. 3 [1,19,27–64]).…”
Section: Resultsmentioning
confidence: 99%
“…2a ), and DVIU was performed using a hot knife at the 3 and 9 o'clock positions. 4 Six months after DVIU, perineal discomfort and left hip pains were observed. PBO and USF extending from the VUAS site to the pubic symphysis were detected on MRI (Fig.…”
Section: Case Reportmentioning
confidence: 99%
“…VUAS was identified 2 years after RT (Fig. 2a), and DVIU was performed using a hot knife at the 3 and 9 o'clock positions 4 . Six months after DVIU, perineal discomfort and left hip pains were observed.…”
Section: Case Reportmentioning
confidence: 99%
“…EAU guidelines highlight rates of 0-11%; however, some studies have reported it to be as high as 88%. 41 Therefore, patient expectations need to be managed prior to the initiation of any treatment. Appropriate counselling regarding the risks of recurrence, potential complications and multiple procedures is key.…”
Section: Research and Reports In Urology 2023:15mentioning
confidence: 99%
“…Shinchi et al reported the first-time success rate of deep BNI approach as 81.4%, but this was matched by an equally high percentage of de novo incontinence. 41 As such, albeit there is evidence to support performing deep BNI down to fat it does not increase the success rate significantly enough to justify the additional risks. 41 These outcomes are also not further improved by combination of simultaneous balloon dilatation, as patency rates for this are similar, and range from 72% to 81% after a single procedure.…”
Section: Endoscopic Proceduresmentioning
confidence: 99%